Analisis Sistem Informasi Formulir Pendftaran Rawat Jalan di RSUD dr. H. MOCH. Ansari Saleh Banjarmasin - Mutia Dewi; Nirma Yunita; Eka Rahma Ningsih (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2024)
The medical record form is used in carrying out the process of recording and processing data in the patient's medical record. The information system on the contents of the outpatient registration form implemented by RSUD dr. H. Moch Ansari Saleh Banjarmasin is guided by or still follows the Regulation of the Minister of Health Number 269/Menkes/Per/III/2008 Article 3 concerning the contents of medical records. This study aims to analyze the information system for outpatient registration forms at dr. H. Moch Ansari Saleh Hospital Banjarmasin in 2023. This type of research uses descriptive qualitative research with data collection methods in the form of observation and interviews with 1 registration officer and head of the medical record unit related to analysis registration form information system. The results of the study are based on anatomical aspects, physical aspects and content aspects. The content aspects are guided or still follow the Regulation of the Minister of Health Number 269/Menkes/Per/III/2008 so that the variables and meta data need to add value to the item name of parents, gender , religion and marital status. And on the user interface for the ease and usefulness of using electronic forms. Based on the results of the study, it can be concluded that dr. H. Moch Ansari Saleh Banjarmasin Hospital to adjust the contents of the registration form is guided by the Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07/MENKES/1423/2022 concerning Guidelines for Variables and Meta Data in the Implementation of Electronic Medical Records. aspects.